A study on spent coffee ground as cement admixtures - Chua, Zhen Yang (2017)
The purpose of carrying out this research is to find out the properties of spent coffee ground and its effect as cement retarding admixtures. The research started with using 0%, 0.2%, 0.4%, 0.6%, 0.8% and 1.0% of SCG being added into mortar mix as retarding admixtures. The proportion of sand to cement to water used in mortar mix design for this research is 2.75: 1: 0.6 according to the standard ASTM C1329-05. Fresh and hardened properties tests were carried out for this mortar mix, namely the flow table test, Vicat test and compressive strength test by using size 50mm x 50mm x 50mm cube. The mortar cubes were cured for 3, 7, 28 and 45 days. X-Ray Diffraction (XRD), X-Ray Florescence (XRF) and SEM EDX were also conducted in order to determine the chemical composition of the spent coffee ground and the microstructure of the mortar after the addition of spent coffee ground as retarding admixtures. The result of the flow table test shows the mortar maintain its flow ability within the standard values after the addition of SCG at various percentage. Moreover, the Vicat test of the SCG mortar shows that the mortar paste containing 0.6 % of SCG and above has retard the initial and final setting time of the mortar. In addition, the compressive strength test recorded that the compressive strength of 0.6 SCG mortar is highest compared to all other SCG mortar and also higher than the control mortar. The 0.6 SCG mortar compressive strength is recorded at 42.857 MPa whereas the control mortar is at 37.345 MPa, 14.76% higher than the control mortar. The XRD and XRF tests show that the major component in SCG are Potassium Oxide, Potassium Sodium Calcium Aluminium Chromium Oxide Silicate, and Tschortnerite. Indeed, the peak of SCG is at 20.20 and it is also found to highly content native cellulose or hemi cellulose. The higher number of C-S-H bond also observed in 0.6 SCG mortar compared to the control mortar, which results in higher compressive strength.